Modeling the Effect of Plug Positions and Ladle Aspect Ratio on Hydrogen Removal in the Vacuum Arc Degasser. Issue 5 (20th February 2018) - Karouni, Faris; Wynne, Bradley P.; Talamantes‐Silva, Jesus; Phillips, Stephen
Abstract : The rate of hydrogen removal from molten steel in a vacuum arc degasser (VAD) is simulated using a three‐phase (slag‐argon‐steel) Eulerian model. The time required to degas a 100 tonne melt from 5 to 1.5 ppm is predicted for a series of ladle aspect ratios and plug layouts. Compared to an axisymmetric single plug system, the degassing time can be reduced by 36% with the use of three equiangular plugs. Increasing the aspect ratio (AR) of the melt from 0.8–1.2 leads to an improvement in degassing performance, followed by a reduction in performance between AR = 1.2–1.6. A radial plug position of 0.5 R is optimal for achieving low hydrogen levels in the melt. Reducing the inter‐plug angle from θ = 180° (for double plug) and θ = 120° (for triple plug) to θ = 45° further reduces this time by 18 and 3.8%, respectively. The fastest rate of hydrogen removal is obtained through the use of three plugs at positioned at an angle of θ = 45° and plug radial position of 0.5 R . Abstract : The influence of argon plug layout and bath height‐to‐diameter (L/D) ratio on vacuum arc degassing of hydrogen is simulated using a CFD‐mass transfer model. Deploying a triple plug arrangment and with a 45° angle between subsequent plugs is favorable to hydrogen removal efficiency, as is the adoption of a melt aspect ratio of around 1.2.